El ’principio de responsabilidad’ de Hans Jonas a la luz de la conciencia ecológica - González Gómez, Germán (Nómadas. Critical Journal of Social and Juridical Science, 2015)
Today we are immersed in a technological era in which human being has the power to dominate nature at will -a power that he prides himself on. This power has got such great dimensions and implications that a new knowledge is strongly required to counter it: possibly, an ethics with predictive power such as Hans Jonas´s imperative of responsibility. The promise of technological progress has become a threat and its environmental consequences have facilitated the emergence of the ecological awareness, giving rise to eco-ethics as its theoretical realization. The link between both ethics is evidenced in the precautionary principle, an attitude of alertness and constraint against the risks of the current technoscientific civilization.